PRAGUE AND CENTRAL-BOHEMIAN INTEGRATED TRANSPORT (Perner's Contacts, 2020)
The article solves the problem of integrated transport systems (ITS) in the Czech Republic. The first part introduces principles of ITS, the second one speaks about history and the two systems operating in the region – the Prague Integrated Transport and the Central-Bohemian Integrated Transport. The last part includes perspectives, the process of merging and weaknesses of integration in the region.
Keywords: integrated transport system; Prague Integrated Transport; Central-Bohemian Integrated Transport